An Image Encryption Algorithm Based on a Novel Five-Dimensional Hyper- Chaotic System - A. Mehdi, Sadiq; M. jasim, Zynab (International Journal of Engineering and Technology, 2018)
According to the fast growth of the Internet and communications networks, you must protect the secrecy of digital images sent over public networks. In recent times, researchers have developed ways to chaotic systems based image encryption. Specific characteristics of the disorder systems, such as dependence on initial conditions sensitivity, pseudorandom, ergodicity and system parameters, chaotic dynamics systems became as a promising alternative to traditional encryption algorithms. In this work, A fresh algorithm is presented to encrypt images depend onÂ a novel five dimensional hyper-chaotic system to achieve High level of security, the chaotic sequence generated from system employ for permutation the original image to create a cipher image. The security of presented encryption algorithm evaluated by much security analysis such as Histogram Analysis, Correlation Coefficient Analysis, Information Entropy Analysis, Key Space Analysis, Key Sensitivity Analysis, Number of Pixels Change Rate (NPCR), Unified Average Changing Intensity (UACI), Peak Signal to Noise Ratio , The experimental results demonstrate that the algorithm has good encryption effect, large key space equals to 10182and high sensitivity to a tiny change in secret key for decrypted images ,therefore, the presented encryption algorithm depend on a novel hyper- chaotic system is more secure against the statistical and deferential attacks.Â Â